Environmental issues in agricultural development/edited by H. Ramachandran - "Ramachandran, H (ed.)" (New Delhi, 1990)
This volume addresses various issues involved in sustainability of our agricultural growth. The central issue is not one concerned with the technology or the institutional factors but of goals of maximizing output of a single product against the maximum of output of resources system, the weights attached to long run as against the short run etc. In order to appreciate this, the social, economic and political aspects of ecological questions have to be increasingly added to the ones dealing with the environmental aspects of ecology.
Keywords: Rural development